"Pelos muitos caminhos de Deus" : possibilidades e limites da teologia pluralista transreligiosa da libertação - Souza, Maruilson Menezes de (2012)
At the beginning of the new millennium a consensus is being formed among scholars from different parts of the world that classical theology no longer responds with satisfaction to the questions of this new Axial time. There is also an increasing desire to build a new theology that is inter-faith, multi-faith or simply trans-religious. This new theology requires the construction of a new paradigm in the theological thinking. Reflecting the efforts of similar initiatives around the world, the Ecumenical Association of Third World Theologians, EATWOT, through the collection "along the many paths of God , proposed a new theology, that is trans-religious, secular, open, non-institutional, global, planetary, multi-religious, pluralist and in connection with the principles of liberation theology. This research ventures to study the possibilities and limits of this proposal of EATWOT.